Student Evaluation of Lecturer Performance Faculty of Engineering, Universitas Negeri Manado - Sumual, Herry; Sumual, Hendro; Ratumbuisang, Keith F (JR Education, 2025)
This study analyzes student evaluations of lecturer performance at the Faculty of Engineering, Manado State University, integrating quantitative and qualitative approaches. A total of 127 students from various study programs assessed four main dimensions of lecturer performance: pedagogical, professional, personality, and social competence. Quantitative results indicate that all dimensions received high average scores, indicating that students perceive lecturer performance to be in the good to excellent category. Qualitative findings reinforce these results and reveal aspects that students appreciate, such as clarity of material delivery, professionalism, communicative interactions, and academic exemplary behavior. However, students highlighted the need for increased innovation in more applicable learning methods, broader use of digital media, and more intensive and constructive evaluation feedback. This study confirms that lecturer performance is a strategic factor in improving the quality of engineering learning and provides recommendations for strengthening engineering pedagogy, digitizing learning, and developing a formative evaluation system within a sustainable quality assurance framework.